Diversity and biogeography of Israeli geophilomorph centipedes (Chilopoda: Geophilomorpha) - Chipman, Ariel D.; Dor, Neta; Bonato, Lucio (Zootaxa, 2013)
The fauna of Chilopoda Geophilomorpha of Israel has been analyzed after examining 128 new specimens from 35 local-ities, reinterpreting all published data including 103 records, and relating occurrence of species with major climatic pa-rameters. A key to identification has been compiled. A total of 17 species are distinguished, of which three are reported from Israel for the first time, while five are documented by published records only. The following new synonymies are proposed and discussed: Dignathodon pachypus Verhoeff, 1943 = Dignathodon microcephalus (Lucas, 1846); Geophilus flavidus noduliger Verhoeff, 1925 = Clinopodes escherichii (Verhoeff, 1896); Pachymerium ferrugineum vosseleri Ver-hoeff, 1902 = P. ferrugineum (Koch, 1835). Of all the species, Bothriogaster signata and Pachymerium ferrugineum are widespread in the country, while other species occupy different climatic zones, from desert to more humid and montane.